LINGUACULTUROLOGICAL ASPECTS OF ADVERTISING TEXTS: CRAFTING MESSAGES THAT TRANSCEND LANGUAGE BARRIERS - Munavvar Amonova (Лучшие интеллектуальные исследования, 2023)
Abstract: This article examines advertising texts and their linguaculturological aspects. The importance of cultural values on the process of making decisions and some potential ways to avoid cultural barrier are provided as well.